New cogeneration concept applied to diesel power generators–Thermal modeling, parametric analysis and first feasibility study - Jalal Faraj; Ahmed Mohsin Alsayah; Mohammed J. Alshukri; Angham Fadil Abed; Samer Ali; Hicham El Hage; Mahmoud Khaled (International Journal of Thermofluids)
In this manuscript, we present a unique cogeneration system that combines diesel power generators with thermoelectric generators (TEGs), using the comparatively cool water in an integrated tank and hot exhaust gases to produce additional heat and power. By connecting a series of TEGs and a cold water tank to the diesel generator, the design enables the water to gradually warm up and become appropriate for usage in both domestic and commercial settings. We did a parametric study and created detailed thermal models to verify the viability of our idea. The findings indicate that the temperature differential across each TEG module and the total power output increase roughly linearly, based on the ratio of the diesel generator's power to the thickness of TEG to thermal conductivity. Additionally, the total power output increases linearly with the length of the TEG plate and declines exponentially with the height of the exhaust gas duct. The system may produce up to 3,223 W more electricity under certain circumstances, such as an exhaust gas duct height of 0.05 m, a TEG plate length of 1 m, and a generator output of 150 kW. This improvement could result in a 2.58 % reduction in fuel consumption and an equivalent increase in total power production when compared to conventional systems. The heater system recovers up to 22.4 kW/m² and can heat 100 liters of water in 0.2 h. According to these results, diesel generators and eventually diesel power plants might use less fuel and have more energy efficiency thanks to the suggested cogeneration technology.